Understanding Traditional Walnut Management System in Forest Communities of Selayar Islands, Indonesia - Pratiwi, Rini; Makkarennu, Makkarennu; Ridwan, Ridwan (Jurnal Wasian, 2025)
This study examines traditional walnut management systems in Onto Village, Selayar Islands, Indonesia, using a Traditional Ecological Knowledge (TEK) framework to understand how forest communities have developed and maintained sustainable resource management practices through generations. Through purposive sampling, 24 walnut farmers were interviewed to document indigenous management practices and utilization patterns associated with heritage trees averaging 40-50 years old. The research reveals a comprehensive five-stage management system—planting, harvesting, drying, peeling, and marketing—developed through accumulated traditional knowledge and continuously refined through practical application. Communities demonstrate sophisticated multi-functional utilization strategies that maximise resource efficiency: kernels serve as food and spices, timber provides construction materials, and shells become fuel for charcoal production. However, significant constraints limit the full potential of this traditional system, including reliance on conventional drying methods, limited processing technology, exclusive marketing of raw products, and absence of systematic replanting programmes, despite favourable market prices (IDR 60,000-100,000/kg). The study demonstrates how traditional ecological knowledge enables sustainable forest resource management whilst providing stable community livelihoods. The documented practices reflect generations of adaptive learning and environmental understanding that maintain both economic benefits and ecological integrity. However, finding highlights the complexities that arise between traditional knowledge and market pressures could emphasizing the importance of developing initiatives that honor traditional practices while also fostering positive economic outcomes. These insights unique contribute to understanding how traditional knowledge can inform sustainable forest management policies and support culturally appropriate development approaches in forest-dependent communities.